The Efficacy of the Law on Domestic Violence in Uganda - Nsamba Javira Lubadde (Uganda Christian University, 2025)
The paper attempts to focus the domestic violence from an analytical perspective. It is pointed out that; The paper also considers the state of the Domestic Violence Act in Uganda. The paper also gives remedies by adopting the various recommendations that the researcher will categorically put to the test. The researcher therefore recommended: awareness campaigns for domestic violence, enforcement of the law and advocacy for human rights, the teaching of Christian religious education to be compulsory as a strategy for moral formation. The church should also intensify its mission out to the people as a way of correcting human error and restoring peace, love, care and harmony in society. Domestic violence is a reality, and many families are victims of domestic violence. It was also revealed that women suffer the most from the problem related to domestic violence as compared to men. Drug abuse was one of the most contributory factors that greatly caused domestic violence, illiteracy, poverty, drunkenness, unemployment and finally culture. The study recommended that the Domestic Relations Act be implemented by the relevant authorities.